The Legal and Judicial Basis for the Positive Role of the Criminal Court Judge in Completing the Missing Evidences - Kadhim, Saja; Abd Alkareem, Ban (Journal of Legal Sciences, 2026)
Each opponent in the case competes to present evidence that supports his claim, with the aim of convincing the criminal judge of his right to what he claims. The criminal judge examines and scrutinizes those facts and decides the dispute in light of the factual elements presented to him in that case. However, sometimes he does not find in the case file enough to clarify the doubts in his mind about the veracity of the incident presented before him The evidence contained therein is not sufficient in itself to convince the criminal judge of the validity of the evidence, so he orders an investigation that he deems necessary to enlighten his belief and to ease his conscience. The incomplete evidence requires intervention by the criminal judge to complete it, and therefore it is not permissible to rely on it alone by the trial court to take it as a reason for ruling a conviction Which makes its role in proof left to the trial court in light of the other evidence presented to it (such as testimony and evidence) that enhances its emotional conviction. This study addresses the legal and judicial basis for the positive role of the criminal judge in completing incomplete evidence, with a focus on the legislation that addressed incomplete evidence and how to deal with it, as the majority of countries did not discuss incomplete evidence clearly, but judicial applications have referred, even directly, to this type of evidence and how to deal with incomplete evidence. The research analyzes case studies of the formation of a criminal judge’s conviction through incomplete evidence, because incomplete evidence does not have the same evidentiary strength as complete evidence, so it requires the judge’s intervention to complete it.